PARAPSYCHOLOGICAL EXPERIENCE AS ANOMALOUS EXPERIENCE PLUS PARANORMAL ATTRIBUTION: A QUESTIONNAIRE BASED ON A NEW APPROACH TO MEASUREMENT. - IRWIN, HARVEY J.; DAGNALL, NEIL; DRINKWATER, KENNETH (Journal of Parapsychology)
When persons report a parapsychological experience, they may typically be asserting 2 occurrences: that of an anomalous or seemingly inexplicable event, and their interpretation of this event in paranormal terms. Previous studies identifying correlates of the report of parapsychological experiences may have confounded these 2 factors. The authors describe a new questionnaire which teases apart the 2 factors and report a survey which applied the new measure to the assessment of several potential correlates, namely, schizotypal tendencies, emotion-based reasoning, suspension of reality testing, and executive dysfunction. Data from a convenience sample recruited online supported the potential utility of the questionnaire, although it has yet to be demonstrated that the 2 underlying factors do have different correlates.